Direct growth and properties of few-layer MoS2 on multilayer graphene prepared by chemical vapor deposition - Sirat, Mohamad Shukri; Johari, Muhammad Hilmi; Mohmad, Abdul Rahman; Mohammad Haniff, Muhammad Aniq Shazni; Ani, Mohd Hanafi; Mat Hussin, Mohd Rofei; Mohamed, Mohd Ambri (Springer Nature, 2022)
The distinctive properties of van der Waals heterostructures that combine two or more two-dimensional materials are of interest due to their potential for highperformance devices. Molybdenum disulfide (MoS2)/graphene has been shown as good photodetectors, sensors and field-effect transistors. However, the progress is restricted due to susceptibility of the single-layer MoS2/graphene to the substrate that affects its properties. Recently, few-layer (FL) MoS2 and multilayer (ML) graphene have shown a fairly good electrical performance. Here, a direct growth of FL MoS2 on the ML graphene approach in chemical vapor deposition is taken to synthesize FL MoS2/ML graphene heterostructure. A comprehensive study on the properties of the FL MoS2/ML graphene heterostructure is conducted. The Raman spectra indicate the presence of typical MoS2 peaks (E12g and A1g modes) and graphene peaks (D, G and 2D bands). The slight graphene-peaks shift is related to the electron transfer from ML graphene to the FL MoS2, deducing a good interfacial interaction between both materials. Referring to the atomic force microscopy images, the thickness of the FL MoS2 and ML graphene is measured around 3 nm and 10 nm, respectively. The X-ray diffraction and transmission electron microscope indicate that the grown FL MoS2 is 3R-phase. Field-effect transistor based on the FL MoS2/ML graphene is fabricated and the estimated carrier mobility is around 1036 cm2 V-1 s-1. Our work highlights the necessity of utilizing FL MoS2/ML graphene for extensive fundamental and application studies.